Porosity development of templated porous carbons dried by vacuum as carbon electrodes for electric double-layer capacitors - Kraiwattanawong, Kriangsak (My University, 2023)
Resorcinol and formaldehyde (RF) resin serves as the carbon precursor for porous carbons and carbon/carbon composites possessing a high specific surface area (SSA). This work presents the porosity improvement by the elimination of cotton fibers (CF) from CF/RF composite hydrogels subsequently exchanged by tertiary butyl alcohol (TBA), dried by vacuum, and carbonized. This route contributes the templated porous carbons (TPC) with an asymmetric structure comprising micropores, mesopores, and macropores. At 0.25 of the CF/RF weight ratio, TPC dried by vacuum apparatus has SSA of 2,102 m2 g−1, whereas TPC dried by evaporation only offers SSA of 663 m2 g−1. Using the vacuum acts as pseudo-freeze drying during TBA removal, forming sponge-like carbon and allowing ultra-high SSA. The electrochemical properties of vacuumed TPCs were analyzed, showing that TPC at 0.25 of the CF/RF weight ratio possessed 626 F g−1 more than TPC at 0.00 of the CF/RF weight ratio which had 392 F g−1 at 200 mA g−1.
Keywords: Electric double layer; Energy storage; Porosity development; Porous carbon